Climate Security Observatory – KENYA. Summary for Policymakers - CGIAR FOCUS Climate Security (CGIAR FOCUS Climate Security, 2022)
One of the fastest growing economies in sub-Saharan Africa with a devolved governance system, Kenya can be characterized as a relatively peaceful context when compared to most of its neighboring countries. However, with impacts of climate variability and extremes along with shocks like COVID-19 and the Russia-Ukraine war widening existing inequalities, Kenya has been facing increasing risks of resource-related violence. While climate may not be directly driving localized conflict dynamics, its context-specific interactions with socio-economic and political factors can shape and exacerbate risks of human insecurity and conflict. This profile, derived from the Climate Security Observatory, answers: 1) HOW does climate worsen the root causes of conflict? 2) WHERE are the most vulnerable areas to climate induced insecurities and risks? 3) WHO are the vulnerable groups to climate and security risks that should be targeted? and 4) WHAT needs to be done to break the cycle between climate and conflict?